PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS PENDEKATAN KETERAMPILAN PROSES PADA MATERI BILANGAN PECAHAN DI KELAS VII SMP NEGERI BUKITTINGGI - Fikriani, Tiara (RC-INSTITUT, 2018)
The learning process is a mandatory note so that the learning objectives are achieved, but suboptimal use of learning materials in school cause low results of student learning. So the development of learning materials is one of the solutions to optimize the learning process. The purpose of this study was to generate a worksheet-based approach students skills in Class VII SMP valid, practical, and effective. This research is research development by using the model development phase Plomp made up the initial investigation phase, development or prototyping, and assessment phase. In the early phase of the investigation carried out needs analysis, analysis of the curriculum, the students, the analysis and the analysis of related concepts of learning problems in math. On the phase of development or prototyping redesign process skills-based approach is categorized, then conducted its own evaluation further validated by experts. Assessment phase of the test done and test the practicalities of limited effectiveness. The practicalities of data retrieved from the now the practicalities of teachers, and the now the practicalities of students. The effectiveness of the data retrieved from the final test results of students. The results showed that categorized the skills-based approach of the resulting process is already valid, practical, and effective. Key words: process, skills, valid, practical, effective